Republic of Mozambique : Financial System Stability Assessment Including Report on the Observance of Standards and Codes on the following topics; Banking Supervision, Payment Systems, and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2004)
The Mozambican financial system has made remarkable progress from mono-banking to a full blown, market-based, financial system. Although Mozambican banks are generally profitable and well capitalized, they are exposed to significant credit risk. A number of reforms are needed to enhance the independence of the central bank, to ensure it has the financial means to conduct its monetary policy under a very low-inflation environment, and to improve banks' appetite for making new credits in the difficult Mozambiques lending environment.